Cultivos isolados e consorciados de segunda safra como estratégia de reforma de pastagem - Sarah Visquetti Pedrão (2024)
Pasture degradation represents a major challenge to the sustainability of agricultural production, requiring management practices that promote soil recovery and increased crop productivity. In this context, the present study evaluated the agronomic performance of different second-season crop succession systems, including cowpea, millet, sorghum, and massai grass, and their effects on the productivity of subsequently cultivated maize and dry matter of massai grass cultivated later. The experiment was conducted at the "Alípio Soares Barbosa" School Farm in Iturama-MG during the 2022/23 growing season in a degraded pasture area. The experimental design was a randomized block design with eight treatments and four replications. Soil analyses were performed before crop implantation, followed by acidity correction and fertilization. Agronomic performance was assessed through measurements of plant population, soil temperature, chlorophyll index, dry and green aerial biomass accumulation, macronutrient cycling, and grain yield. The results indicated that the millet + massai consortium presented the highest accumulated biomass values (19.83 t ha⁻¹), promoting better nutrient cycling and increasing subsequent maize productivity (8,055 kg ha⁻¹). Cowpea, in turn, demonstrated biological nitrogen fixation capacity, increasing chlorophyll levels in the succeeding crop. Sorghum in monoculture stood out in terms of dry biomass (12.05 t ha⁻¹) and grain yield (3,494 kg ha⁻¹), confirming its efficiency in degraded areas. Meanwhile, the sorghum + massai treatment proved efficient in maintaining pasture after harvest, ensuring the continuity of the production system. Additionally, the analyses showed that intercropping systems favored greater macronutrient absorption (N, P, K, Ca, Mg, and S), significantly influencing maize yield. The presence of massai grass in the system contributed to greater biomass accumulation and improved moisture retention, positively impacting the following crop. It is concluded that the use of intercropping systems, especially those involving millet and massai grass, is a promising strategy for the recovery of degraded areas, promoting improvements in soil fertility and agricultural productivity. Crop diversification has proven to be an efficient tool for building more sustainable production systems, allowing for greater resilience to climatic variations and contributing to food security and economic stability for farmers.